Health Optimism: The Impact of Health Information Seeking and Healthcare Satisfaction - Saadati, Seyed Milad; Karstensen , Valerie (Journal of Personality and Psychosomatic Research (JPPR), 2025)
The objective of this study was to investigate the relationships between health information seeking, healthcare satisfaction, and health optimism among adults. Specifically, the study aimed to determine how health information seeking and healthcare satisfaction predict health optimism. A cross-sectional design was employed, involving 194 participants recruited through convenience sampling from various community health centers. Data were collected using standardized tools: the Health Optimism Scale, the Health Information National Trends Survey (HINTS), and the Patient Satisfaction Questionnaire Short-Form (PSQ-18). Descriptive statistics, Pearson correlation coefficients, and linear regression analysis were conducted using SPSS-27 to examine the relationships between the variables and to assess the predictive power of health information seeking and healthcare satisfaction on health optimism. Descriptive statistics revealed a mean health optimism score of 3.85 (SD = 0.75), a mean health information seeking score of 4.12 (SD = 0.68), and a mean healthcare satisfaction score of 3.96 (SD = 0.82). Pearson correlation analysis indicated a moderate positive correlation between health information seeking and health optimism (r = 0.42, p < 0.001) and a stronger positive correlation between healthcare satisfaction and health optimism (r = 0.56, p < 0.001). The regression analysis showed that both health information seeking (B = 0.32, SE = 0.09, β = 0.34, t = 3.67, p < 0.001) and healthcare satisfaction (B = 0.47, SE = 0.08, β = 0.45, t = 5.88, p < 0.001) were significant predictors of health optimism, explaining 40% of the variance (R² = 0.40, p < 0.001). This study demonstrates that both health information seeking and healthcare satisfaction significantly contribute to health optimism among adults. Healthcare satisfaction has a slightly stronger influence on health optimism. These findings underscore the importance of improving health information accessibility and the quality of healthcare services to enhance health outcomes and patients’ positive health outlook.